Effect of low-temperature annealings on mechanical properties and evolution of nanostructured alloy Zr1Nb - Sokolenko, V.I.; Karaseva, E.V.; Mats, A.V.; Savchuk, E.S.; Frolov, V.A. (Functional Materials, 2017)
The processes of internal stresses relaxation in Zr1Nb nanocrystalline alloy after low-temperature annealing were studied. The relationship of structural states obtained as a result of annealings with the regularities of development of plastic deformation at creep was established. It is shown that heat treatments of Zr1Nb nanostructured alloy, which provide the increase of the plasticity, change qualitatively the alloy structure, destruct the nanostructured state that results in decrease of the mechanical characteristics of the material and the degree of resistance to subsequent deformation during the creep at the temperature of 700 K.